Atypical and anaplastic meningiomas in a public hospital in São Paulo State, Brazil - Benedicto Oscar Colli; Carlos Gilberto Carlotti Junior; João Alberto Assirati Junior; Vicente de Paulo Martins Coelho Junior; Luciano Neder (Arquivos de Neuro-Psiquiatria)
Atypical/anaplastic (World Health Organization (WHO) grades II and III) are less common and have poorer outcomes than benign meningiomas. This study aimed to analyze the outcome of patients with these tumors.Method Overall/recurrence-free survivals (RFS) and the Karnofsky Performance Scale of 52 patients with grades II (42) and III (9) meningiomas surgically treated were analyzed (uni/multivariate analysis).Results Total/subtotal resections were 60.8%/35.3%. Patients <60 years-old and grade II tumors had longer survival. Grade II tumors, total resection andde novo meningioma had better RFS (univariate analysis). Patients >60 years-old, de novo meningioma and radiotherapy had longer survival and patients <60 years-old and with grade II tumors had longer RFS (multivariate analysis). Recurrence rate was 51% (39.2% Grade II and 66.7% Grade III). Operative mortality was 1.9%.Conclusion Age <60 years-old, grade II tumors and de novomeningiomas were the main predictors for better prognosis among patients with grades II and III meningiomas.